STUDY OF GROWTH YIELD AND SEED QUALITY OF CUCUMBER (Cucumis sativus L.) ON BIOFERTILIZER AND LIQUID SMOKE FERTILIZER - Bayu Aji Pratama; Ami Suryawati; Alif Waluyo (Techno LPPM, 2022)
The application of biofertilizer and liquid smoke fertilizer is either method to increase the production of cucumber according to the environmentally friendly because it’s made from organic materials. The purpose of this research is to get the biofertilizer dose and the best concentration of the liquid smoke fertilizer to increase the growth and yield of fruit as well as the quality of seed cucumber. This research method is a field experiment that arranged by Completely Randomized Group Design (RAKL). The first factor is biofertilizer dose (P) that consist of 3 levels, that is: 5 ml/plant, 10 ml/plant and 15 ml/plant. The second factor is the concentration of the liquid smoke fertilizer (O) that consist of 3 levels that is: 1%, 2% and 3%. The control crops were fertilized according to the farmer’s habit of using NPK without biofertilizer and liquid smoke fertilizer treatment. The obtained data were analyzed by diversity analysis level 5%. To find out the significant differences between the control and the treatment, we did Contras Orthogonal Test level 5% and  Duncan Multiple Distance Test level 5%. The result showed that the combination of treatment was significantly better than the control. There is an interaction between the dose of  biofertilizer and concentration of liquid smoke on the vigor index parameter. The combination of P2O2 (biofertilizer 10 mL/plant and liquid smoke 2%) treatment is the best treatment on vigor index parameter.  The best P2 (dose of biofertilizer 10 mL/plant) treatment was on the parameter of fruit weight per plant. O2 (concentration of liquid smoke 2%) treatment was best on the parameters of fruit weight per swath.